MEDICAL AND SOCIAL DETERMINANTS OF ODONTOGENIC PHLEGMON IN ADOLESCENTS OF THE FERGANA REGION: ETIOLOGICAL FACTORS, EPIDEMIOLOGICAL PATTERNS AND PREVENTIVE STRATEGIES - Gulbadanbegim Abdullayeva Sherzodbekovna (Research Focus International Scientific Journal, 2026)
Odontogenic phlegmon represents one of the most severe purulent-inflammatory complications of dental origin, characterized by rapid spread through fascial spaces and high risk of systemic involvement. Adolescents constitute a particularly vulnerable group due to transitional biological processes, behavioral patterns, and limited health awareness. The present article provides a theoretical and analytical synthesis of medical and social determinants contributing to the development of odontogenic phlegmon among adolescents in the Fergana region. Emphasis is placed on etiopathogenesis, age-related susceptibility, regional epidemiological tendencies, and comparative prevalence patterns in Central Asia, Uzbekistan, Europe, and North America. The study is grounded on analysis of peer-reviewed articles, dissertations, and international medical databases. Findings demonstrate that untreated dental caries, delayed access to dental care, inadequate oral hygiene practices, and socioeconomic disparities are principal drivers of odontogenic infections progressing to phlegmon. Preventive strategies require integration of clinical dentistry, public health education, school-based screening programs, and community-level interventions. The article highlights the necessity of multidisciplinary prevention models addressing both biological and social components of disease formation. Strengthening preventive dentistry, improving healthcare accessibility, and promoting adolescent health literacy are essential for reducing disease burden. The presented analysis supports the development of region-specific preventive policies and reinforces the importance of early intervention.